Controversial role of mast cells in NSCLC tumor progression and angiogenesis. Issue 21 (4th October 2022) - Longo, Vito; Catino, Annamaria; Montrone, MIchele; Galetta, Domenico; Ribatti, Domenico
Abstract: Mast cells (MCs) are multifunctional immune cells implicated in both physiological and pathological processes. Among the latter, MCs play a crucial role in cancer. Many studies have shown a correlation between MCs and tumor progression in several solid and hematological malignancies. In particular, MCs can directly promote tumor growth via c‐kit/stem cell factor–dependent signaling and via the release of histamine, which modulate tumor growth through H1 and H2 receptors. At the same time, MCs can increase tumor progression by stimulating angiogenesis via both proangiogenic cytokines stored in their cytoplasm, and by acting on the tumor microenvironment and extracellular matrix. With regard to NSCLC, the role of MCs has not yet been established, with studies showing a correlation with a poor prognosis on the one hand and suggesting a protective effect of MCs on the other hand. These controversial evidences are at least, in part, due to the heterogeneity of the studies exploring the role of MCs in NSCLC, with some studies describing only the MC count without specification of the activation and degranulation state, and without reporting the intratumoral localization and the proximity to other immune and cancer cells. A better knowledge of the role of MCs in NSCLC is mandatory, not only to define their prognostic and predictive proprieties but also because targeting them could be a possible therapeutic strategy. Abstract : MCs have multiple roles in NSCLC with both protumor and antitumor capabilities according to the tumor context. MCs express a large quantity of molecules promoting tumor progression such as histamine, SCF, FGF‐2, IL‐8, VEGF, PDGF, and NGF. At the same time MCs secrete TGF‐β and TNF‐α, molecules with ambivalent features, able to exert both antitumoral and tumorigenic effects based on the context. Moreover, MCs produce serine proteases activating metalloproteinases and remodeling the extracellular matrix (ECM). In particular, tryptase can degrade the ECM increasing the space available for neovascularization and releasing angiogenic factors included in the matrix. At the same time, tryptase activates PAR‐2 inducing endothelial cell proliferation. Another serine protease, namely chymase, induces angiogenesis by converting angiotensin I to angiotensin II. On the other hand, MCs can contribute to tumor rejection by activating dendritic cells and inhibiting Treg cells and myeloid‐derived suppressor cells (MDSCs). Moreover, chondroitin sulfate, which is secreted by MCs, inhibits the development of metastasis.